Agricultural and Related Pest Control Applicator License Classifications under the Florida Department of Agriculture and Consumer Services (FDACS) - Frederick M. Fishel (EDIS)
This guide provides an explanation of private, public and commercial pesticide applicator licenses issued by FDACS under Chapter 487 Florida Statutes. This document is PI-59, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.